Electrocatalysis: Bifunctional Electrocatalytic Activity of Boron‐Doped Graphene Derived from Boron Carbide (Adv. Energy Mater. 17/2015). Issue 17 (September 2015) - Vineesh, Thazhe Veettil; Kumar, M. Praveen; Takahashi, Chisato; Kalita, Golap; Alwarappan, Subbiah; Pattanayak, Deepak K.; Narayanan, Tharangattu N.
<x xml:space="preserve">Abstract</x> A single material that can perform water splitting and oxygen reduction reactions, known as a bifunctional catalyst, is a novel concept used in modern energy technologies, such as regenerative fuel cells. In article number 1500658, Subbiah Alwarappan, Deepak K. Pattanayak, Tharangattu N. Narayanan, and co‐workers report the favorable bifunctional catalytic properties of a nanoparticle‐free, graphene‐based material that is derived from rhombohedral boron carbide using a novel fabrication route.